HASIL AUDIT DAN OPINI YANG DIHASILKAN SEHUBUNGAN MUNCULNYA TEMUAN KECURANGAN DAN PENGARUH PENGALAMAN AUDITOR - Kencana Putra Antariksa, Galih (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This study examines the impact of fraud findings in procurement processes and the level of auditor experience on audit results, using a case study of Company X. Company X experienced significant financial performance changes in the form of increases, followed by fraud incidents during the audit period. The research employs a qualitative approach with data collected through interviews and examination of audit evidence. The findings indicate that significant fraud findings and the level of auditor experience critically influence the audit results and the opinion issued. The study emphasizes the importance of thorough and careful risk assessment and the need for auditors to adjust their audit strategies in response to new evidence, including fraud findings. Additionally, the research highlights the necessity for robust internal controls and the auditor's role in ensuring the accuracy and reliability of financial statements. The results suggest that when significant fraud is detected, auditors must reassess risks, adjust audit procedures, and issue an appropriate opinion that reflects the true state of the financial statements.